Una carta en torno al escudo de armas de Mateo Vázquez de Leca en la "Corsica" de Calvete de Estrella - Díaz Gito, Manuel Antonio (Calamus Renascens: revista de humanismo y tradición clásica, 2009)
Edition and commentary of a letter from the historian and poet Juan Cristóbal Calvete de Estrella to Philip II´s secretary, Mateo Vázquez de Leca. Calvete´s letter deals with a fragment of his poem Corsica in which the coat of arms of the Corsican family Lecca is accurately described; this is the first part of a study where the conection of this letter to the obscure lineage of Mateo Vázquez is analysed.